Nutrition of ageing black South African women and correlates with anthropometry and cardiometabolic outcomes - Kankwende, Caroline Belinda Tsitsi (University of the Witwatersrand, Johannesburg, 2023)
Background: Obesity is most prevalent among black women who reside in urban areas in South Africa yet the nutrient patterns of this cohort of women has never been investigated, nor have correlates of body composition indices such as adiposity and body mass index (BMI). These body composition indices are important to analyse as they have been shown to be positively associated with hypertension which is prevalent in this cohort of women. Aim: There were three main goals: 1) To determine the baseline nutrient patterns of middle-aged black South African women residing in Soweto and correlates to body composition indices 2) To evaluate the longitudinal association of nutrient patterns with adiposity in a cohort of middle-aged black South African women over a period of 5.5- years 3) To elucidate the longitudinal associations of nutrient patterns and blood pressure and to explore whether this is an indirect effect mediated by body mass index (BMI) using structural equation modelling Methods: A longitudinal study of children and their families, originally called the Birth to Twenty Plus (Bt20+) cohort and now referred to as the Middle-aged Soweto Cohort (MASC), was used to as the original dataset for this thesis. This study also drew on another embedded study, the Study of Women Entering and in Endocrine Transition (SWEET) study of older women transitioning through menopause. Data on (i) dietary information; (ii) body composition and anthropometry measurements; (iii) blood pressure; (iv) lifestyle behaviours (physical activity, tobacco use, and alcohol use); (v) psychosocial factors; (vi) socioeconomic status; and (vii) educational status were used. A total of 498 Women aged between 40 and 60 years old were included in the study. Principle component analysis (PCA) was applied on the dietary data both at baseline and at 5- years follow-up. This was conducted to extract nutrient patterns from 25 nutrients derived from the food frequency questionnaire (FFQ) and the resulting nutrient patterns are detailed in results chapter 3 (nutrient patterns derived from the baseline FFQ) and results chapter 4 (comparison between both baseline and follow-up nutrient patterns from the FFQ). Simple and complex body composition were recorded for each participant with complex body measurements taken using (DXA). Chapter 3 details the results of the 3 baseline nutrient patterns and correlates with body composition parameters. Using generalized estimating equations, associations between both baseline and 5- years follow-up nutrient patterns and adiposity were evaluated. The results are discussed in results chapter 4. Lastly, the results chapter 5 examined associations between both baseline and follow-up nutrient patterns and blood pressure were examined and furthermore, investigated whether BMI mediates the relationship between repeated measures of nutrient patterns and blood pressure. Results: The majority of the research participants (88%) were classified as individuals having obese status defined by their BMI. The fat mass index (FMI), lean mass index (LMI), gynoid fat, hip and waist circumference, and visceral and subcutaneous adipose tissue (VAT and SAT respectively) measurements were all substantially larger in the group with predominantly individuals having overweight and obese classification compared to woman in the lean group (p <0.001). Protein consumption was greater in the group with individuals having overweight/obese classification, while fat and carbohydrate consumption were matched. At baseline, the "Plant driven nutrient pattern," characterized by higher factor loadings of plant protein, starch, and B vitamins, explained 25% of the total nutritional variance; the "Animal protein driven nutrient pattern," characterized by animal protein and saturated fat, explained 23% of the variance; and the third pattern was the "Vitamin C, sugar and potassium driven nutrient pattern," which had higher factor loadings of vitamin C, sugar and potassium. At baseline, increased consumption of the animal protein driven nutrient pattern resulted in a 1.19 kg/m2 (p = 0.002) increase in BMI, 10.17 cm2 for VAT, 24.43 cm2 for SAT, 0.01 (p = 0.009) increase for VAT/SAT ratio, 0.69 kg/m2 (p = 0.005) increase for FMI, and 0.48 kg/m2 (p = 0.002) increase for LMI. Furthermore at baseline, statistically significant associations were found for the animal protein driven nutrient pattern with all body composition indicators. Subcutaneous adipose tissue increased in the presence of a plant-driven nutrition pattern (p = 0.045). At 5-year follow-up, although the value of the factor loadings of the individual nutrients changed between baseline and follow-up, the nutrients with the highest loadings for each principal component (PC) did not change therefore the overall nutrient patterns remained the same. Only DXA-derived measurements of fat mass, FMI, VAT, and gynoid fat mass (FM) increased with time, while lean mass considerably reduced. Repeated measures of the animal protein driven nutrient pattern was associated with significant increases in FMI, LMI and VAT and repeated measures of the vitamin C, sugar, and potassium driven nutrient pattern was significantly associated with an increase in FMI and LMI. For the purposes of this study, repeated measures of animal-driven nutrient patterns were shown to be significantly related with repeated measures of systolic blood pressure (SBP) only. When structural equation modelling (SEM) was applied, only significant relationships were observed between age and SBP. This relationship was not mediated by BMI but may involve other factors that were not included in this analysis. Conclusions: This thesis explored the nutrient patterns linked to obesity and cardiometabolic complications, namely blood pressure, in a cohort of black middle-aged African females. It has been previously demonstrated that this cohort has been has a high prevalence of obesity. According to literature reviews, programs focusing on nutritional and behavioural changes could aid African women in their fight against the obesity and hypertension epidemic that we are facing today. The animal-driven nutrient pattern was found to be substantially associated with increases in body fat in this cohort at baseline. At 5-year follow-up, the nutrient patterns remained the same and repeated measurements of the vitamin C, sugar, and potassium-driven nutrient pattern were associated with significant increases in FMI and LMI and the animal-driven nutrient pattern remained significantly associated with LMI, FMI and VAT, a measure of visceral obesity which is a major risk factor for cardiometabolic conditions. This is problematic in a population that consists predominantly of individuals that are classified as having an obese and overweight status. As a result of a higher BMI, a greater likelihood of developing cardiometabolic multimorbidity exists which is defined as the co-occurrence of two or three cardiometabolic conditions. This may result in reduced quality of life and an increased burden on the already overstretched healthcare system in South Africa. Furthermore, this study found that only the animal protein driven nutrient pattern had a significant relationship with SBP which was significant. When SEM was applied, BMI did not mediate the relationship between blood pressure and any of the nutrient patterns. No other noteworthy direct relationships between blood pressure and the other nutrient patterns were found. Researchers can apply the findings of this study to improve nutritional policies and guidelines aimed at combating not just obesity, but high blood pressure among black women in Sub-Saharan Africa. It is necessary to conduct further extensive research to verify these findings.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy, to the Faculty of Health Sciences, School of Clinical Medicine, Department of Paediatrics and Child Health, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Nutrient patterns; Cardiometabolic outcomes; Black South African woman; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education